Costs and health effects of screening and delivery of hearing aids in Tamil Nadu, India: an observational study - Job Anand; Balraj Achamma; Monica Priya; Vinod J Abraham; Rob Baltussen; Norman Gift; Joseph Abraham (BMC, 2009)
Abstract Background The burden of disease of hearing disorders among adults is high, but a significant part goes undetected. Screening programs in combination with the delivery of hearing aids can alleviate this situation, but the economic attractiveness of such programs is unknown. This study aims to evaluate the population-level costs, effects and cost-effectiveness of alternative delivering hearing aids models in Tamil Nadu, India Methods In an observational study design, we estimated total costs and effects of two active screening programs in the community in combination with the provision of hearing aids at secondary care level, and the costs and effects of the provision of hearing aids at tertiary care level. Screening and hearing aid delivery costs were estimated on the basis of program records and an empirical assessment of health personnel time input. Household costs for seeking and undergoing hearing health care were collected with a questionnaire (see Additional file 2). Health effects were estimated on the basis of compliance with the hearing aid, and associated changes in disability, and were expressed in disability-adjusted life years (DALYs) averted. Results Active screening and provision of hearing aids at the secondary care level costs around Rs.7,000 (US$152) per patient, whereas provision of hearing aids at the tertiary care level costs Rs 5,693 (US$122) per patient. The cost per DALY averted was around RS 42,200 (US$900) at secondary care level and Rs 33,900 (US$720) at tertiary care level. The majority of people did consult other providers before being screened in the community. Costs of food and transport ranged between Rs. 2 (US$0,04) and Rs. 39 (US$0,83). Conclusion Active screening and provision of hearing aids at the secondary care level is slightly more costly than passive screening and fitting of hearing aids at the tertiary care level, but seems also able to reach a higher coverage of hearing aids services. Although crude estimates indicate that both passive and active screening programs can be cautiously considered as cost-effective according to international thresholds, important questions remain regarding the implementation of the latter.